2012
DOI: 10.1002/clen.201100303
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Interaction Mechanism in the Biosorption of Copper(II) Ions onto Posidonia oceanica and Peat

Abstract: A systematic approach was used to characterize the biosorption of copper(II) onto two biosorbents, Posidonia oceanica and peat, focusing on the interaction mechanisms, the copper(II) sorption–desorption process and the thermal behavior of the biosorbents. Sorption isotherms at pH 4–6 were obtained and the experimental data were fitted to the Langmuir model with a maximum uptake (qmax) at pH 6 of 85.78 and 49.69 mg g−1, for P. oceanica and peat, respectively. A sequential desorption (SD) with water, Ca(NO3)2, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…These shifts suggested that chemical coordination takes place on the surface of the biomass between ionizable functional groups and metal ions. These ideas have already been incorporated by other authors in more recent papers (12,(41)(42)(43).…”
Section: Results and Discussion Adsorption Featuresmentioning
confidence: 84%
“…These shifts suggested that chemical coordination takes place on the surface of the biomass between ionizable functional groups and metal ions. These ideas have already been incorporated by other authors in more recent papers (12,(41)(42)(43).…”
Section: Results and Discussion Adsorption Featuresmentioning
confidence: 84%
“…2d). The spectral bands at 3175-3490 cm −1 are assigned to O H stretching intra-molecular hydrogen bonds for cellulose I, 2850-2970 cm −1 to C H stretching and the signal at 1511 cm −1 is associated to the aromatic ring present in lignin (Cocozza et al, 2011;Coletti et al, 2013;Izquierdo et al, 2012;Salapare Iii et al, 2013). The FT-IR spectra of bleached fibres and CNC from P. oceanica confirmed the results already observed in the thermogravimetric analysis: after chemical treatment, the band at 1511 cm −1 was absent, confirming the removal of the lignin fraction.…”
Section: Resultsmentioning
confidence: 99%
“…These proteins have the capacity to bind heavy metals through the thiol groups, which are also known as sulfhydryl groups (R-SH), and amino groups (R-NH 2 ) of its cysteine residues [24], [25]. Other studies have investigated the biosorption of heavy metals such as copper, lead, and chromium, and the removal of dyes from textile waters using P. oceanica biomass [21], [26][30].…”
Section: Introductionmentioning
confidence: 99%